A comprehensive comparative study on mid-term clinical and functional outcomes in Indian patients following bilateral total knee arthroplasty: assessing the impact of body mass index on post-total knee arthroplasty results - Ponnanna, Karineravanda Machaiah; Rudraraju, Ravi Teja; Bajwa, Supreet; Aneja, Kunal (International Journal of Research in Orthopaedics, 2024)
Background: Limited research exists on Indian obese patients undergoing simultaneous bilateral total knee arthroplasty (bTKA), necessitating a comprehensive and comparative analysis with non-obese counterparts. This study presents an observational and prospective assessment of Indian patients who underwent cruciate retaining/posterior stabilized (CR/PS) metal-backed implant surgeries from 2016 to 2019. Methods: The study encompassed 190 patients (380 knees) undergoing bTKA, classified by World Health Organization (WHO) weight stratification: normal weight (cohort 1, n=51), overweight (cohort 2, n=85), and obese (cohort 3, n=54). Primary endpoints were implant survivorship and revision rates, with secondary endpoints including range of motion (ROM), knee society score (KSS), Western Ontario and McMaster Universities osteoarthritis index (WOMAC), and SF-36 scores. Results: Female representation dominated all groups (88.24%, 87.06%, and 90.74%). End-stage osteoarthritis occurred in 94.12%, 96.47%, and 98.15%, respectively. Over the 3-year follow-up, four fatalities occurred, with 186 patients completing the study. ROM showed significant improvement after three years, with baseline values increasing from 93.29°±18.29° (cohort 1) to 123.97°±2.28°, 122.86°±5.03°, and 122.67°±4.77°, respectively (p<0.001). KSS demonstrated substantial improvement (cohort 1: 89.87±6.48, cohort 2: 90.47±8.40, cohort 3: 90.52±8.07) after three years. A 100% success rate and no revisions indicated implant durability. WOMAC and SF-36 questionnaires exhibited significant improvements in pain, stiffness, and overall well-being (p<0.001) after bTKA. Conclusions: This mid-term CR/PS knee survival analysis underscores 100% implant functionality, improved knee function, and enhanced quality of life for all patients, irrespective of their body mass index (BMI). Simultaneous bilateral TKA with CR/PS implants demonstrates favourable outcomes, affirming its efficacy as a viable treatment option.